(3GdQSGdI GdaJMjI aj GdCYeGd GdLjHjIs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI agPg QSGdI ai GdYed HGdQHY GdeLjH eTJedg Ydi ebOeI hYTQjf HGHkG s
(3BNQgG (B:s
(3aeG Hbi agh Yeb Pdc HGdCLRGA GdJi LRFJ efgG bWQ ae GdHjQ s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B167 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B52 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B80) s
Keywords: (3Gdadcs